ALIGINING THE NATIONAL ASSESSMENT SYSTEM OF UZBEKISTAN WITH TIMSS 2023 STANDARDS: PSYCHOMETRIC AND INSTITUTIONAL IMBALANCES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article presents an analysis of the results of experiments conducted to determine the biological effectiveness of chemical preparations against root pests of pear seedlings - cockchafer (Scarabaeidae) beetles. Bifstar 10% em.k (bifenthrin) was selected as the chemical preparation, which was used at a consumption rate of 1 l/ha. This article explores the alignment of Uzbekistan’s national education quality assessment system with the requirements of the TIMSS 2023 international program. Within the scope of the study, national assessment criteria and institutional management mechanisms were examined using systematic analysis and gap analysis methods. The results of the analysis revealed a significant imbalance among cognitive domains within national assessment tests. Furthermore, the insufficient application of psychometric tools (specifically the Item Response Theory model) and the prevalence of vertical management styles were identified as key factors hindering the effectiveness of educational management. To address the identified disparities, the study concludes with strategic recommendations focused on enhancing the legal framework, the phased implementation of modern psychometric models, and the capacity building of professional staff.